Effects of natural gas composition on performance and regulated, greenhouse gas and particulate emissions in spark-ignition engines. (1st July 2017) - Amirante, R.; Distaso, E.; Di Iorio, S.; Sementa, P.; Tamburrano, P.; Vaglieco, B.M.; Reitz, R.D.
Highlights: The influence of natural gas composition is investigated. Real-time methane/propane fuel mixtures were realized. IMEP, HRR and MBF were used to evaluate the effects on engine performance. Gaseous, greenhouse and Particulate emissions were studied. The propane content strongly influenced performance and emissions. Abstract: In vehicles fueled with compressed natural gas, a variation in the fuel composition can have non-negligible effects on their performance, as well as on their emissions. The present work aimed to provide more insight on this crucial aspect by performing experiments on a single-cylinder port-fuel injected spark-ignition engine. In particular, methane/propane mixtures were realized to isolate the effects of a variation of the main constituents in natural gas on engine performance and associated pollutant emissions. The propane volume fraction was varied from 10 to 40%. Using an experimental procedure designed and validated to obtain precise real-time mixture fractions to inject directly into the intake manifold. Indicative Mean Effective Pressure, Heat Release Rate and Mass Burned Fraction were used to evaluate the effects on engine performance. Gaseous emissions were measured as well. Particulate Mass, Number and Size Distributions were analyzed with the aim to identify possible correlations existing between fuel composition and soot emissions. Emissions samples were taken from the exhaust flow, just downstream of the valves. Opacity was measured downstream the Three-Way Catalyst. Three different engine speeds were investigated, namely 2000, 3000 and 4000 rpm. Stoichiometric and full load conditions were considered in all tests. The results were compared with pure methane and propane, as well as with natural gas. The results indicated that both performance and emissions were strongly influenced by the variation of the propane content. Increasing the propane fraction favored more complete combustion and increased NOx emissions, due to the higher temperatures. In all tests, natural gas showed the highest PN values. At high speeds, adding propane increased the number of particles between 5 and 30 nm, highlighting the relevance of the ultrafine particles. Smaller differences were recorded at low speeds.